Diet and trophic niche of Antarctic silverfish Pleuragramma antarcticum in the Ross Sea, Antarctica. Issue 1 (12th December 2012) - Pinkerton, M. H.; Forman, J.; Bury, S. J.; Brown, J.; Horn, P.; O'Driscoll, R. L.
Abstract : The diet of Antarctic silverfish Pleuragramma antarcticum was evaluated by examining stomach contents of specimens collected in the Ross Sea (71°–77° S; 165°–180° E) in January to March 2008. Pleuragramma antarcticum (50–236 mm standard length, L S ) and prey items were analysed for stable‐isotopic composition of carbon and nitrogen. According to index of relative importance ( I RI ), which incorporates frequency of occurrence, mass and number of prey items, the most important prey items were copepods (81% I RI over all specimens), predominantly Metridia gerlachei and Paraeuchaeta sp., with krill and fishes having low I RI (2·2 and 5·6% I RI overall). According to mass of prey ( M ) in stomachs, however, fishes ( P. antarcticum and myctophids) and krill dominated overall diet (48 and 22% M, respectively), with copepods being a relatively minor constituent of overall diet by mass (9·9% M ). Piscivory by P. antarcticum occurred mainly in the extreme south‐west of the region and near the continental slope. Krill identified to species level in P. antarcticum stomachs were predominantly Euphausia superba (14·1% M ) with some Euphausia crystallophorias (4·8% M ). Both DistLM modelling (PRIMER‐permanova+) on stomach contents (by I RI ) and stepwise generalized linear modelling on stable isotopes showed that L S and location were significant predictors of P. antarcticum diet. Postlarval P. antarcticum (50–89 mm L S ) consumed exclusively copepods. Juvenile P. antarcticum (90–151 mm L S ) consumed predominantly krill and copepods by mass (46 and 30% M, respectively). Small adult P. antarcticum (152–178 mm L S ) consumed krill, fishes and copepods (37, 36 and 15% M, respectively). Large adult P. antarcticum (179–236 mm L S ) consumed predominantly fishes and krill (55 and 17% M, respectively), especially in the north (near the Ross Sea slope) and in the SW Ross Sea. Amphipods were occasionally important prey items for P. antarcticum (western Ross Sea, 39% M ). General concordance between stomach contents and trophic level of P. antarcticum and prey based on δ 15 N was demonstrated. Pleuragramma antarcticum trophic level was estimated as 3·7 (postlarval fish) and 4·1 (fish aged 3+ years).